Effect of drought stress on bending stiffness in petioles of Caladium bicolor (Araceae)1. Issue 11 (1st November 2013) - Caliaro, Marco; Schmich, Florian; Speck, Thomas; Speck, Olga
Abstract : Premise of the study: Cell turgor plays an important role in the mechanical stability of herbaceous plants. This study on petioles of Caladium bicolor 'Candyland' analyzes the correlation between flexural rigidity and cell turgor. The results offer new insights into the underlying form–structure–function relationship and the dependency of mechanical properties from water availability. Methods: Bending modulus E of petioles is calculated from two‐point bending tests, taking into account the tapering mode. The corresponding turgor of parenchyma cells during wilting is investigated by pressure probe tests. Key results: Wilting petioles show highly significant lower values of E than petioles with sufficient water supply. These differences are also found when comparing well‐watered petioles to drought‐stressed petioles having parenchyma turgor values in the same range. These results indicate an additional mechanical system sensitive to drought stress. On the basis of analyses of the contribution of different petiolar tissues toward the axial second moment of area and by using experimentally determined and literature values of E for the different tissues, we were able to (1) recalculate E of the intact petiole and to compare it with experimental data and (2) quantitatively estimate the importance of the different tissues for flexural rigidity and E of the petiole. Conclusions: Our results show that the decrease in flexural rigidity of petioles of Caladium bicolor 'Candyland' during wilting results from (1) a water‐loss‐induced decrease in mechanical efficiency of collenchyma fibers and (2) turgor loss of parenchyma cells.